2011
DOI: 10.7763/ijcea.2011.v2.79
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nanotechnology in Solar PV Cell

Abstract: The solar cell industry has grown quickly in recent years due to strong interest in renewable energy and the problem of global climate change .Cost is an important factor in the success of any solar technology. Today's solar cells are simply not enough efficient and are too expensive to manufacture for large-scale electricity generation. However, potential advancements in nanotechnology may open the door to the production of cheaper and slightly more efficient solar cells. Nanotechnology has already shown huge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 3 publications
1
22
0
4
Order By: Relevance
“…The figure explained that this kind of enhancement adds nearly $3.5 million to the yearly revenue of a large solar power plant. Sethi et al [37] explained that using nano-structured layers in thin film solar cells offered three important advantages. First, due to multiple reflections, the effective optical path for absorption was much larger than the actual film thickness.…”
Section: Solar Cells Typesmentioning
confidence: 99%
“…The figure explained that this kind of enhancement adds nearly $3.5 million to the yearly revenue of a large solar power plant. Sethi et al [37] explained that using nano-structured layers in thin film solar cells offered three important advantages. First, due to multiple reflections, the effective optical path for absorption was much larger than the actual film thickness.…”
Section: Solar Cells Typesmentioning
confidence: 99%
“…The disposal of the toxic Cd based materials as well as their recycling can be highly expensive and damaging too to our environment and society [10] [24]. Therefore, a limited supply of cadmium and environmental hazard associated with its use are the main issues with this CdTe technology [26]- [29].…”
Section: Cadmium Telluride (Cdte) Thin Film Solar Cellmentioning
confidence: 99%
“…The author concluded that there is a need of further innovation in this technology since the material used degrades in due course of time and due this efficiency decreases. [4] have studied the use of nanotechnology in solar cells. The method to implement nano crystals in solar cells for better performance and efficiency is proposed.…”
Section: Types Of Solar Cellsmentioning
confidence: 99%